Parenting Patterns Applied by Parents to Children Aged 3-6 Yearsat ST. Francis Assisi Delitua Kindergarten in 2023 - Jagentar P.Pane; Ernita Rante Rupang; Alvi Maldova (International Journal of Health and Medicine, 2024)
This research begins with the understanding that parenting styles are one of the key factors influencing children's behavior, personality, and socio-emotional development. Thus, positive behavior in children largely depends on the application of appropriate parenting styles. The method used in this research is a descriptive design. The sample was taken using total sampling technique, with a total of 64 respondents. The instrument used in this study was a questionnaire. The results showed that the majority of the parenting style applied was democratic, with 64 respondents (100%), authoritarian with 13 respondents (20%), permissive with 17 respondents (26%), 14 parents applied two parenting styles, and 8 parents applied three parenting styles. **Conclusion:** This research is expected to serve as a reference for maximizing the implementation of effective parenting styles according to the child's developmental stage, which will have a more positive impact on the child's overall growth and development.